The Routledge companion to twentieth-century philosophy - Moran, Dermot (Routledge philosophy companions., 2008)
"The Routledge Companion to Twentieth Century Philosophy is a survey and assessment of the major figures, themes, and movements in twentieth-century philosophy. Featuring twenty-two chapters written by leading international scholars, this Companion is divided into five clear parts and presents a comprehensive picture of the period."--BOOK JACKET.